Evaluasi Program Pelatihan Soft Skill Mahasiswa: Pendekatan Experimental Research - Astuty, Isthofaina (208-7721)
The objective of this research was to evaluate student soft skill training program, especially on student satisfaction toward soft skill training execution, student understanding of training material, identification of self efficacy level (before and after training) and the training impact to the student behavior. 31 student from management Department were involved in this research. Mean analisys and paired sample t test were used to analyze data. The results showed that (i) student were satisfied with training execution in all aspecs (ii) student understood with training material (iii) there was a difference level of self efficacy (before and after training) (iv) student behavior changing didnât need long time.